The prognostic strength of serum LDH and serum ferritin in children with neuroblastoma: A report from the International Neuroblastoma Risk Group (INRG) project. Issue 8 (30th May 2020) - Moroz, Veronica; Machin, David; Hero, Barbara; Ladenstein, Ruth; Berthold, Frank; Kao, Paige; Obeng, Yaa; Pearson, Andrew D.J.; Cohn, Susan L.; London, Wendy B.
Abstract: Purpose: Age, MYCN status, stage, and histology have been used as neuroblastoma (NB) risk factors for decades. Serum lactate dehydrogenase (LDH) and serum ferritin are reproducible, easily obtained, and prognostic, though never used in risk stratification, except one German trial. We analyzed the prognostic strength of LDH and ferritin, overall, within high‐risk NB, and by era, using the International Neuroblastoma Risk Group Data Commons. Patients and methods: Children with NB (1990‐2016) were categorized into LDH ( n  = 8867) and ferritin ( n  = 8575) risk groups using EFS. Cox models compared the prognostic strength of LDH and ferritin to age, MYCN status, and INSS stage. Results: Higher LDH conferred worse EFS, overall (5‐year EFS) (100‐899 IU/L: 76 ± 0.6%; 0‐99 or 900‐1399 IU/L: 60 ± 1.2%; ≥1400 IU/L: 36 ± 1.2%; P  < .0001), and in high‐risk NB post‐2009 (3‐year EFS) (117‐381 IU/L: 67 ± 8.9%; 382‐1334 IU/L: 58 ± 4.4%; 0‐116 or ≥1335 IU/L: 46 ± 3.9%; P  = .003). Higher ferritin conferred worse EFS, overall (5‐year EFS) (1‐29 ng/mL: 87 ± 0.9%; 0 or 30‐89 ng/mL: 74 ± 0.8%; ≥90 ng/mL: 48 ± 0.9%; P  < .0001), and in high‐risk NB post‐2009 (3‐year EFS) (1‐53 ng/mL: 71 ± 9.3%; 0 or 54‐354 ng/mL: 55 ± 4.7%; ≥355 ng/mL: 34 ± 6.1%; P  = .0008). In multivariable analyses adjusting for age, MYCN, and stage, LDH and ferritin maintained independent prognostic ability ( P  < .0001; adjusted HRs (95% CI): 1.7 (1.5‐1.9), 2.3 (2.0‐2.7), respectively). Conclusions: LDH and ferritin are strongly prognostic in NB, overall and within high‐risk NB patients treated post‐2009 with modern therapy. LDH and ferritin show promise for (a) identifying ultra‐high‐risk; (b) refining risk stratification; and (c) clinical utility in low‐/middle‐income countries. Routine collection of LDH and ferritin should be reinitiated for evolving NB risk stratification.